Skrining dan Identifikasi Bakteri Selulolitik Tempat Pemakaman Umum - Siti Nur Syarifah; Erma Musbita Tyastuti; Yasir Sidiq; Triastuti Rahayu (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to determine the potential of cellulolytic bacteria and identify bacterial isolates originating from TPU. A total of 36 bacterial isolates that will be tested for their cellulolytic potential have been isolated from Pracimaloyo Kartasura TPU, Sukoharjo. Selection of cellulolytic bacteria used selective Carboxymethyl Cellulose (CMC) media dripping with 0.1% Congo red while identification was based on colony morphology and Gram staining. The research results showed that 8 bacterial isolates (22.22%) showed positive cellulolytic activity, namely P5, P8, P10, P14, P22, P25, P27, and P31, with a cellulolytic index value of 7.5; 5; 6.25; 7; 7, 5, 25; 7, 25; and 6.5. Cellulolytic positive isolates have shiny white colonies, entire edges, raised elevations, and are classified as Gram negative cocci. The conclusion of this research is that TPU public burial places harbor potential cellulolytic bacteria. Keywords: Cellulolytic Bacteria, Public Cemetery (TPU), Pracimaloyo